PREDICTING INFLAMMATORY REACTION AFTER CATARACT PHACOEMULSIFICATION - Анна Сергеевна Попова; Александр Леонидович Онищенко; Сергей Николаевич Филимонов; Раиса Михайловна Зорина; Анна Егоровна Власенко (Медицина в Кузбассе, 2018)
Currently, phacoemulsification is the «gold» standard of cataract surgery. In a number of cases, post-surgical complications can develop in the form of an inflammatory reaction of varying degrees of severity. The purpose of the study was to develop a method for predicting the inflammatory reaction after phacoemulsification of cataract (PEC) by analyzing the clinical and immunological status of the patients.